Knowledge of the context, behavior, and expectations of miners in relation to the tin mining policies and practices in Bangka Belitung - Ibrahim Ibrahim; Dwi Haryadi; Nanang Wahyudin (Faculty of Social and Political Science, Universitas Airlangga, 2018)
In the last two decades, tin mining in Bangka Belitung Islands has operated in controversy, between groups who oppose the idea of unconventional mining and those expecting the mining to be carefully performed. This is as well as prioritizing sustainability principles. Amidst the controversy, the unconventional mining methods conducted by local people have been preserved. This writing has observed the miners’ perspective of their profession. This study used quantitative methods to explore the miners’ knowledge, context, behavior, and expectations of the politics of tin mining policies and its practices. The data analysis used was frequency table and Kendall’s Tau-b correlation by applying SPSS version 20 Program. This study found that miners were generally aware that the tin wealth in this region provided great contributions to the economy sector. They also realized that their mining broke the regulation and understood that the benefits they gained were less than that gained by businessmen. The miners’ behaviour also showed awareness that mining damages the environment. A behaviour of hesitation was shown in whether they were ready or not to change their profession, the easiness of finding another job, and whether the mining situation that they worked in should be forbidden or firmly dealt with. Nevertheless, the miners hope that recent conditions can be maintained rather than restricted. This study concluded that there were inconsistent political policies at the implementation level, strengthened by the weakness of law culture in society.